The effects of measurement basis and slack benefits on honesty in budget reporting - Church, Bryan K.; Kuang, Xi (Jason); Liu, Yuebing (Sarah) (Accounting, Organizations and Society, 2019)
In this study, we experimentally investigate how managers' budget reporting behavior is influenced by two important features of the budgeting system: the measurement basis used in budget preparation (i.e., whether managers make budget reports in financial or nonfinancial measures) and managers' slack benefits in budget execution (i.e., whether managers benefit from budgetary slack directly or through an intermediate activity). While prior research suggests that moral self-regulation helps promote honest behavior, we predict that a financial measurement basis undermines moral self-regulation by strengthening the manager's desire to advance self-interest and that the absence of direct slack benefits undermines moral self-regulation by making misreporting more justifiable. We also predict that the effects of these two budgetary features on honesty are non-additive, due to the manager's diminishing marginal net utility from misreporting. Experimental results are consistent with our predictions. The implications of our findings for management accounting theory and practice are discussed.